Metaphoric perceptions of individuals with diabetes in Turkey: A content analysis - Aslı Tok Özen; Özlem Bulantekin Düzalan; Betül Yalçın (Belitung Nursing Journal, 2024)
Background: The diagnosis of diabetes mellitus adversely impacts the quality of life due to treatment, changes in daily life, functional disability, and emerging complications. Using metaphors to convey perceptions of diseases and life experiences is crucial for understanding healthcare behaviors.